2021
DOI: 10.1111/1365-2664.13879
|View full text |Cite
|
Sign up to set email alerts
|

How hydrological connectivity regulates the plant recovery process in salt marshes

Abstract: 1. Designing effective restoration strategies is a priority in recovering salt marsh plants. Hydrological connectivity is a main driver underpinning the success of the plant recovery process and can regulate life-history process-based restoration strategies. However, the relationship between these is unclear.2. Plant recovery needs to go through a whole life-history process, from seed to adult. Common restoration strategies are seed addition (SA) or seedling transplantation (ST), which start from seed germinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…There have been surprisingly multiple studies reporting hydrological connectivity above the soil surface for managers or governments to restore wetlands or create new wetlands (Chen et al, 2016; Jiang et al, 2021; Zhao et al, 2019). For example, high hydrological connectivity above the soil surface will disrupt the survival of the autochthonous producers in coastal salt marshes and damage wetland ecosystem services (Yin et al, 2020), whereas Wang et al (2021) found that hydrological connectivity above the soil surface could improve soil physical and chemical properties, such as reducing soil compactness and soil salinity and increasing soil water content. However, our understanding of hydrological connectivity below the soil surface remains an extreme gap in our recent works.…”
Section: Introductionmentioning
confidence: 99%
“…There have been surprisingly multiple studies reporting hydrological connectivity above the soil surface for managers or governments to restore wetlands or create new wetlands (Chen et al, 2016; Jiang et al, 2021; Zhao et al, 2019). For example, high hydrological connectivity above the soil surface will disrupt the survival of the autochthonous producers in coastal salt marshes and damage wetland ecosystem services (Yin et al, 2020), whereas Wang et al (2021) found that hydrological connectivity above the soil surface could improve soil physical and chemical properties, such as reducing soil compactness and soil salinity and increasing soil water content. However, our understanding of hydrological connectivity below the soil surface remains an extreme gap in our recent works.…”
Section: Introductionmentioning
confidence: 99%
“…Above 6 m can be correspondingly expressed as poor and worst hydrological connectivity strength. Vegetation growth in different cycles also has different hydrological requirements (Wang et al 2021 ). The next step will also be to further quantify the relationship between vegetation response to hydrological connectivity in different growth cycles to provide more detailed suggestions for wetland hydrological connectivity restoration.…”
Section: Discussionmentioning
confidence: 99%
“…The high marsh has a low tidal flood frequency of 1 to 15% in terms of number of days per year ( 69 ). The soils are characterized by a hypersaline condition with salinity of up to 25 parts per thousand and present accumulated salts on the surfaces regularly ( 69 , 70 ). The salt marshes are primarily dominated by the annual succulent plant species Suaeda .…”
Section: Methodsmentioning
confidence: 99%
“…Salicornia europaea , Phragmites australis , Tamarix chinensis , and the invasive cordgrass Spartina alterniflora are also found in the Yellow River Delta ( 71 ). The vegetation in our study site is monospecific ( Suaeda ), presenting a sparse vegetation cover around 5% ( 70 ). Regular spatial patterning of Suaeda vegetation following self-organized mud cracking is clearly observed in the field (Fig.…”
Section: Methodsmentioning
confidence: 99%